NutriWise Mobile App Design for Daily Nutrition Recommendations Based on User Preference - Mar’atullatifah, Yulaikha; Mahmudah, Himmatunnisak; Prasetyo, Deni; Fauzi, Muhammad Anwar; Tamtomo, Agatha Pricilia Sekar (Ali Institute of Research and Publication, 2025)
Nutritional imbalances caused by modern lifestyles and limited awareness of healthy eating remain widespread issues requiring technology-driven solutions. This study aims to design and evaluate a mobile application prototype, NutriWise, that provides daily meal recommendations tailored to users' nutritional needs and preferences. A User-Centered Design (UCD) approach was employed, involving users throughout the stages of requirement analysis, interface design, and initial prototype evaluation. The results indicate that the application is easy to use, delivers relevant meal suggestions, and supports nutritional monitoring through food logging and visual tracking features. These findings are supported by previous studies emphasizing the effectiveness of personalization and user-centered approaches. The study offers practical contributions to the development of adaptive digital solutions for daily nutrition management